Role of folding kinetics of secondary structures in telomeric G-overhangs in the regulation of telomere maintenance in Saccharomyces cerevisiae - Jurikova, Katarina; Gajarsky, Martin; Hajikazemi, Mona; Nosek, Jozef; Prochazkova, Katarina; Paeschke, Katrin; Trantirek, Lukas; Tomaska, Lubomir (The Journal of biological chemistry, 2020)
The ends of eukaryotic chromosomes typically contain a 3' ssDNA G-rich protrusion (G-overhang). This overhang must be protected against detrimental activities of nucleases and of the DNA damage response machinery and participates in the regulation of telomerase, a ribonucleoprotein complex that maintains telomere integrity. These functions are mediated by DNA-binding proteins, such as Cdc13 in Saccharomyces cerevisiae, and the propensity of G-rich sequences to form various non-B DNA structures. Using CD and NMR spectroscopies, we show here that G-overhangs of S. cerevisiae form distinct Hoogsteen pairing-based secondary structures, depending on their length. Whereas short telomeric oligonucleotides form a G-hairpin, their longer counterparts form parallel and/or antiparallel G-quadruplexes (G4s). Regardless of their topologies, non-B DNA structures exhibited impaired binding to Cdc13 in vitro as demonstrated by electrophoretic mobility shift assays. Importantly, whereas G4 structures formed relatively quickly, G-hairpins folded extremely slowly, indicating that short G-overhangs, which are typical for most of the cell cycle, are present predominantly as single-stranded oligonucleotides and are suitable substrates for Cdc13. Using ChIP, we show that the occurrence of G4 structures peaks at the late S phase, thus correlating with the accumulation of long G-overhangs. We present a model of how time- and length-dependent formation of non-B DNA structures at chromosomal termini participates in telomere maintenance.
Keywords: Electrophoretic Mobility Shift Assay; homeostáza telomer; Kinetics; telomerase; kinetika; Oligonucleotides; DNA, Single-Stranded; jednovláknová DNA; Nucleic Acid Conformation; telomere; konformace nukleové kyseliny; G-quadruplex; G-hairpin; Telomere Homeostasis; cell cycle; proteiny vázající telomery; telomery; retardační test; oligonukleotidy; Telomerase; Saccharomyces cerevisiae; Saccharomyces cerevisiae - proteiny; DNA-Binding Proteins; G-Quadruplexes; folding kinetics; G-kvadruplexy; DNA; Cdc13; telomerasa; Telomere-Binding Proteins; Saccharomyces cerevisiae Proteins; Telomere; DNA vazebné proteiny